Effects of Milk Thistle (Silybum marianum) Seed Supplementation to High-Calorie Basal Diets of Quails on Egg Production, Egg Quality Traits, Hatchability and Oxidative Stress Parameters - Erisir, Zeki; Iflazoglu Mutlu, Seda; Simsek, Ulku Gulcihan; Ciftci, Mehmet; Azman, Mehmet Ali; Benzer, Fulya; Erisir, Mine (Kafkas Univ, Veteriner Fakultesi Dergisi, 2016)
The purpose of this study was to examine the changes to occur in egg production, egg quality traits, hatchability, and oxidative stress parameters of laying quails fed with high calorie diets and effect of milk thistle (Silybum marianum) seed on these changes. A total of 75 45-day-old quails including 60 females and 15 males were used in the study. The quails were divided into 5 groups with three repetitions. 4 females and 1 male were used in each repetition. The groups of the study were arranged as following; control group (C) consuming corn-soybean based basal diet, oil group (SFO) in which 5% sun flower oil was added into basal diet, oil + milk thistle group (SFO+MT) in which 5% sun flower oil + 1% milk thistle seed was added into basal diet, syrup group (CS) in which 10% corn syrup was added into basal diet, and syrup + milk thistle group (CS+MT) in which 10% corn syrup + 1% milk thistle was added into basal diet. Total egg production was found to be significantly higher in SFO and SFO+MT groups of present study (P<0.05). Feed intake, total egg weight and feed conversion were found similar among the groups (P>0.05). The differences among the groups in albumen rate, yolk rate, dried shell rate and shape index were not statistically significant (P>0.05). The best yolk colour was obtained in SFO+MT and CS groups (P<0.01). There were no statistically differences among the groups in hatchability, hatchability of fertile and embrionic mortality (P>0.05), but the difference in examined fertility were statistically significant (P<0.05). Malonyl dialdehyde (MDA) values of blood, liver and heart tissues were similar among the groups of study (P>0.05). MDA level of kidney significantly increased in CS group, however addition of milk thistle seed into diet was reduced MDA level of kidney in CS+MT group (P<0.01). High calorie diets caused changes in antioxidant system in blood and tissues. Consequently, high-calorie basal diets especially addition of SFO improved only egg production and fertility rate. However feeding quails with corn syrup had significantly higher lipid peroxidation in kidney. Supplementation of milk thistle seed into CS group may protect kidney against free radical damage.
Yüksek kalorili bıldırcın karma yemlerine deve dikeni (Silybum marianum) tohumu ilavesinin yumurta verimi, yumurta kalite özellikleri, kuluçka randımanı ve oksidatif stres parametreleri üzerine etkisi
Keywords: Quail; Egg yield; hatchability; Milk thistle; High calorie diets; Oxidative stress